2021
DOI: 10.4193/rhin20.588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of house dust mite immunotherapy in mono- versus poly-sensitised patients with allergic rhinitis: a systematic review and meta-analysis

Abstract: Selecting an appropriate allergen-specific immunotherapy (AIT) regimen for polysensitised allergic rhinitis (AR) patients is challenging for clinicians. Although previous studies showed comparable effectiveness of single-allergen AIT with house dust mite (HDM) extract between monosensitised and polysensitised AR patients, there is no systematic review and meta-analysis demonstrating the comparable effectiveness of HDM AIT. In this meta-analysis, we analysed nine studies to compare the clinical effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Since HDM is the only tablet approved for patients with non‐seasonal AR, data regarding polysensitized patients is important. Kim et al 2661 . reported a meta‐analysis of HDM AIT in mono‐ or polysensitized patients.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Since HDM is the only tablet approved for patients with non‐seasonal AR, data regarding polysensitized patients is important. Kim et al 2661 . reported a meta‐analysis of HDM AIT in mono‐ or polysensitized patients.…”
Section: Managementmentioning
confidence: 99%
“…Since 2017, numerous SRMAs were identified for SLIT tablets (Table XI.D.6.a.‐1). Eight reported both aqueous and tablet SLIT, 2426,2438,2636,2637,2644,2661–2663 six presented aqueous and tablet SLIT separately, 2438,2550,2638,2639,2664,2665 and nine reported on tablet SLIT alone 1982,1986,1995,2532,2636,2640,2646,2651,2672 . All studies reported outcomes for HDM, grass pollen, and/or ragweed pollen.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis study of HDM AIT in mono and poly-sensitized patients with AR found no significant differences in the nasal symptom score, medication score, or quality of life between the groups. The study concluded that single-allergen AIT using HDM was clinically effective for both mono and poly-sensitized AR patients ( 152 ). Component-resolved diagnosis is essential for avoiding the inclusion of irrelevant allergens in mixed shots.…”
Section: The Efficacy In Armentioning
confidence: 99%
“…These inflammatory factors further promote B cells to secrete antigen-specific IgE (sIgE). When the allergen restimulates the immune process of the body, sIgE binds quickly to the allergen epitope and crosslink occurs, which makes mast cells degranulate and release allergic and inflammatory mediators, damage nasal mucosa and lead to AR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%